Reproduction of Meloidogyne enterolobii in lettuce cultivars of the american group - Correia, Érika C. S. S. [UNESP]; Silva, Norberto [UNESP]; Costa, Marylia G. S. [UNESP]|Wilcken, Silvia R. S. [UNESP] (Associação Brasileira de Horticultura, 2015)
Lettuce is the main vegetable cultivated in Brazil, in volume and in marketed value. There are ranges of diseases which may affect lettuce crops, including those caused by root-knot nematodes (Meloidogyne spp.). We evaluated the reproductive potential of Meloidogyne enterolobii in 22 lettuce cultivars. The plants were inoculated with 5,000 eggs and eventuals second stage juveniles of nematode per pot, two days after the transplanting. 'Rutgers' tomato was used as standard for inoculum viability of M. enterolobii. We evaluated, 60 days after inoculation, the gall index, egg mass index and reproduction factor (RF). The 'Ithaca', 'Raider Plus', 'RS-1397', 'L-104', 'Challenge', 'IP-11', 'Classic', 'Salinas 88', 'Vanguard 75', 'Calona' and 'Desert Queen' were resistant to M. enterolobii with RF varying from 0.22 to 0.9, and the cultivars Lady Winterset, Robinson, Sonoma, Raider, Lucy Brown, Bnondaga, Summer Time, Taina, Sundevil and L-109 were susceptible to this nematode, with RF ranging from 1.06 to 5.73.

A alface é a principal hortaliça folhosa cultivada no Brasil, tanto em volume como em valor comercializado. Em áreas de cultivo, a alface tem a sua produtividade comprometida por diversas enfermidades, incluindo as causadas pelos nematoides-das-galhas (Meloidogyne spp). Este trabalho teve como objetivo avaliar o potencial reprodutivo de Meloidogyne enterolobii em vinte e duas cultivares de alface do tipo americana. As plantas foram inoculadas com 5.000 ovos e eventuais juvenis de segundo estádio de M. enterolobii por vaso, dois dias após o transplante das cultivares. O tomateiro 'Rutgers' foi utilizado como padrão de viabilidade do inóculo de M. enterolobii. Foram avaliados o índice de galhas (IG), índice de massas de ovos (IMO) e fator de reprodução (FR) do nematoide, aos 60 dias após a inoculação. As cultivares Ithaca, Raider Plus, RS-1397, L-104, Challenge, IP-11, Classic, Salinas 88, Vanguard 75, Calona e Desert Queen apresentaram resistência a M. enterolobii, com FR variando de 0,22 a 0,9, e as cultivares Lady, Winterset, Robinson, Sonoma, Raider, Lucy Brown, Bnondaga, Summer Time, Tainá, Sundevil e L-109 foram suscetíveis a esse nematoide, com FR variando de 1,06 a 5,73.
Multiplicação de Meloidogyne enterolobii em cultivares de alface do grupo americano
Keywords: Lactuca sativa; Root-knot nematodes; Plant breeding; Lactuca sativa; Nematoide-das-galhas; Melhoramento genético